Infraestrutura física e integraç\~ao regional na América do Sul: Uma avaliaç\~ao da iniciativa para a integraç\~ao da infraestrutura regional da América do Sul - Carlos Eduardo Lampert Costa; Manuel José Forero Gonzales (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The main goal of this work is to assess the Initiative for the Integration of Regional Infrastructure in South America (Iirsa), launched in September 2000, during the First Meeting of the Presidents of South America, held in Brasilia, Brazil. The aim of this initiative was, at first, to foster the physical integration of the subcontinent in order to increase productivity and competitiveness and achieve higher economic growth and development. The starting point was the observation that one of the main obstacles to the region's development was infrastructure deficit. In this sense, the text is focused on analyzing the evolution of this initiative, seeking to identify the main advances and difficulties regarding its implementation. By doing that, lessons can be learned concerning the design of public policies for regional integration, considering that the Iirsa is one of the most ambitious physical integration programs ever developed in the region.
Keywords: N76; F15; 330; economic integration; integration of physical infrastructure; Iirsa; competitiveness